Penerapan Path Analysis terhadap Faktor-Faktor yang Mempengaruhi IPM dan Kemiskinan di Indonesia Tahun 2019 - Andika Nikola Putra; Helen Fricylya Br Tobing; Ossy Sanityasa Rahajeng; Risni Julaeni Yuhan (Universitas Negeri Surabaya, 2020)
Poverty is a complex and multidimensional problem so that it becomes a development priority. One of the measurement tools commonly used in seeing the quality of human life is the human development index. The purpose of this study is to analyze the HDI in Indonesia including poverty which is a general impact. The analysis was conducted using the Path Analysis method approach which is an extension of the regression analysis. The factors that had the greatest influence on HDI values in Indonesia in 2019 were Life Expectancy, then Regional Original Income, then Old School Expectations and who had the smallest influence and had a negative effect on HDI values in Indonesia in 2019 were the Number of Hospitals. The factor that has the greatest influence and has a negative influence on the percentage of poor population in Indonesia in 2019 is the Human Development Index, and another factor that also affects the percentage of poor population in Indonesia in 2019 is Hope for School Duration.